Neutral-color low-internal-reflection temperable three-silver low-emissivity coated glass

By setting up a multi-layer film structure on Sanyin low-radiation coating glass, the problem of the existing technology being unable to meet the neutral transmission color, low indoor reflectivity and tempering at the same time, achieving better optical performance and application applicability.

CN222593723UActive Publication Date: 2025-03-11SICHUAN NANBO ENERGY SAVING GLASS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202420721694.7
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-04-09
Publication Date
2025-03-11
Estimated Expiration
2034-04-09

AI Technical Summary

Technical Problem

The existing tri-silver low-radiation coating glass cannot meet the performance requirements of neutral transmission color, low indoor reflectivity and temperable.

Method used

By setting a multi-layer film structure on the glass substrate, including silicon nitride, zinc oxide, silver, AZO, copper and nickel-chromium alloy, the thickness and composition of each film layer are adjusted, and prepared by magnetron sputtering coating technology.

Benefits of technology

It realizes the neutral transmission color, low indoor reflectivity and tempering effect of coated glass, which is suitable for large-scale promotion and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222593723U_ABST
    Figure CN222593723U_ABST
Patent Text Reader

Abstract

The utility model discloses temperable three-silver low-emissivity coated glass with neutral color and low internal reflection. Comprising a glass substrate and a film layer, and the film layer is arranged on the surface of the glass substrate; the film layer sequentially comprises a first silicon nitride layer with the thickness of 20-30 nm, a second zinc oxide layer with the thickness of 10-15 nm, a third silver layer with the thickness of 5-10 nm, a fourth AZO layer with the thickness of 3-5 nm, a fifth silicon nitride layer with the thickness of 30-40 nm, a sixth zinc oxide layer with the thickness of 10-15 nm and a seventh silver layer with the thickness of 10-15 nm from the glass substrate to the outside. The coated glass can simultaneously meet the performance requirements of neutral transmission color, low indoor reflectivity and temperable property, and is suitable for large-scale popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model relates to the field of coated glass materials, in particular to a neutral color low internal reflection temperable triple silver low radiation coated glass. Background Art

[0002] With the large-scale production and application of triple-silver low-E glass and the continuous improvement of people's demand for glass quality and personalization, the existing triple-silver low-E glass has exposed many problems that need to be improved.

[0003] Among them, patent CN218290755U discloses a low-reflection, ultra-clear, neutral-color triple-silver low-radiation coated glass. Through the arrangement of the coating layers and the optimization design of the coating process, the entire coated glass is neutral in color and has good light transmittance. The coated glass is favored by the market because of its advantage of neutral transmitted color and more realistic outdoor environment color. However, the coated glass also has the problem that it cannot be tempered after coating, which is obviously not conducive to the installation and application of the coated glass and is not suitable for large-scale promotion and application.

[0004] Among them, China CN106186723B discloses a medium-transmittance light blue bendable steel triple-silver low-emissivity coated glass and its preparation process, which achieves the effect of toughening the film layer by compounding eighteen film layers in sequence on a glass substrate and restricting the thickness of the film layers in a targeted manner. However, the film layer structure is relatively complex, which is not conducive to large-scale production, and the transmittance color of the coated glass is light blue, which is not conducive to observation of the outdoor environment.

[0005] Among them, China CN 212152091U discloses a low-radiation coated glass, which combines different film layer materials and sets the film thickness to achieve strong energy-saving performance, a transmittance color close to a neutral color, and low indoor reflection. However, the coated glass is double-silver glass, and its performance in energy saving and emission reduction is lower than that of triple-silver glass. It also has the defect of being unable to be tempered, and is not suitable for large-scale promotion and application.

[0006] It can be seen that the current triple-silver low-emissivity coated glass cannot simultaneously meet the performance requirements of neutral transmitted color, low indoor reflectivity and temperability. Utility Model Content

[0007] The invention purpose of the utility model is to propose a neutral color low internal reflection temperable triple silver low emissivity coated glass in view of the above defects of the existing triple silver low emissivity coated glass.

[0008] In order to achieve the above purpose, the technical solution adopted by the utility model is:

[0009] A neutral color low internal reflection temperable triple silver low emissivity coated glass, comprising a glass substrate and a film layer, wherein the film layer is arranged on the surface of the glass substrate; wherein the film layer comprises, from the glass substrate outward, a first silicon nitride layer with a thickness of 20-30nm, a second zinc oxide layer with a thickness of 10-15nm, a third silver layer with a thickness of 5-10nm, a fourth AZO layer with a thickness of 3-5nm, a fifth silicon nitride layer with a thickness of 30-40nm, a sixth zinc oxide layer with a thickness of 10-15nm, a third silver layer with a thickness of 5-10nm, a fourth AZO layer with a thickness of 30-40nm, a fifth silicon nitride layer with a thickness of 30-40nm, a sixth zinc oxide layer with a thickness of 10-15nm, a third silver ...0nm, a third silver layer with a thickness of 10-10nm, a third silver layer with a thickness of 10-10nm, a third silver layer with a thickness of 10-10 A seventh silver layer with a thickness of 0-15nm, an eighth copper layer with a thickness of 3-6nm, a ninth nickel-chromium alloy layer with a thickness of 1-3nm, a tenth AZO layer with a thickness of 5-10nm, an eleventh zinc oxide tin layer with a thickness of 60-70nm, a twelfth zinc oxide layer with a thickness of 10-20nm, a thirteenth silver layer with a thickness of 10-15nm, a fourteenth nickel-chromium alloy layer with a thickness of 1-3nm, a fifteenth AZO layer with a thickness of 3-5nm, and a sixteenth silicon nitride layer with a thickness of 30-40nm.

[0010] The utility model discloses a neutral color, low internal reflection, temperable triple-silver low-radiation coated glass. Through the targeted design of the film layer material, structure, protective layer thickness and interference layer thickness, not only the transmitted color is neutral, thus ensuring good appearance color and performance; but also the glass has a lower indoor reflectivity, so that there will be no obvious reflected image on the indoor surface under the night light, and the user's indoor experience is more comfortable; at the same time, the bonding stability between the film layers is better, so that the film layers are defect-free after tempering, the color performance is stable, and the temperable effect is achieved; the coated glass can simultaneously meet the performance requirements of neutral transmitted color, low indoor reflectivity and temperability, and is suitable for large-scale promotion and application.

[0011] Among them, preferably, the thickness of the first silicon nitride layer is 22-25nm; the thickness of the fifth silicon nitride layer is 35-38nm; the thickness of the sixteenth silicon nitride layer is 34-36nm; the preferred thickness of the silicon nitride layer provides a better appearance effect of the coated glass.

[0012] Among them, preferably, the thickness of the third silver layer is 6-8nm; the thickness of the seventh silver layer is 12-14nm; the thickness of the thirteenth silver layer is 10-12nm; with the preferred thickness of the silver layer, the coated glass has better radiation resistance, better energy-saving effect, and lower internal reflection.

[0013] Among them, preferably, the thickness of the ninth nickel-chromium alloy layer is 2-3nm; the thickness of the fourteenth nickel-chromium alloy layer is 1-2nm; the preferred nickel-chromium alloy layer thickness has a better protective effect on the silver layer.

[0014] Among them, preferably, the thickness of the eleventh zinc tin oxide layer is 65-68 nm; with the preferred thickness of the zinc tin oxide layer, the appearance of the coated glass is better.

[0015] Among them, preferably, the thickness of the second zinc oxide layer is 12-14nm; the thickness of the sixth zinc oxide layer is 11-13nm; the thickness of the twelfth zinc oxide layer is 12-15nm; the preferred zinc oxide layer thickness, the inter-layer bonding strength of the coated glass is better, can better block the penetration of reactive ions, and ensure stable color performance after tempering.

[0016] Among them, preferably, the thickness of the fourth AZO layer is 4-5 nm; the thickness of the tenth AZO layer is 6-8 nm; the thickness of the fifteenth AZO layer is 3-4 nm; the preferred AZO layer thickness has a better protective effect on the silver layer.

[0017] Preferably, the eighth copper layer has a thickness of 4-5 nm. With a preferred copper layer thickness, the color of the coated glass after tempering is more neutral and the internal reflection is lower.

[0018] The utility model can be prepared by adopting magnetron sputtering coating technology. It is plated in sequence under a high vacuum background. The preparation method is simple, mature and suitable for industrial production. The obtained glass can be used for building curtain walls, can achieve good appearance effects, and can better meet the lighting, aesthetic and energy-saving requirements of buildings.

[0019] In summary, due to the adoption of the above technical solution, the beneficial effects of the utility model are:

[0020] 1. The neutral color, low internal reflection, tempered triple-silver low-emissivity coated glass of this utility model has a neutral transmission color, ensuring good appearance color and performance; the optical properties are as follows:

[0021] performance T / R (%) L* a* b* Glass surface reflection color 17~19 48~50 -2.5~-3.0 -6~-9 Glass surface small angle reflection color 18~20 50~52 -3.5~2.5 -7~-9 Film surface reflection color 5~7 30~35 -3~-5 -6~-9 Transmittance Color 50~55 75~80 -2~-3 +1~+2

[0022] ; Note 1: The transmittance a* value of the tempered triple silver products on the market is generally in the range of [-9, -5], which is greenish, and the b* value range is [+4, +8], which is yellowish;

[0023] Note 2: In order to quantitatively describe and measure color, the CIE1976L*a*b* color space is generally used internationally to measure color: L or R is generally used to represent brightness, and the two have a certain conversion relationship. The value is in the range of 0-100, and the larger the value, the higher the brightness; a* is used to represent redness and greenness, a negative a* represents green, a positive a* represents red, and the larger the absolute value, the greater the degree of green or red; b* is used to represent yellowness and blueness, a negative b* represents blue, a positive b* represents yellow, and the larger the absolute value, the greater the degree of yellow or blue; the closer a* and b* are to zero, the more neutral the transmitted color is.

[0024] 2. The neutral color, low internal reflection, tempered triple-silver low-emissivity coated glass of this utility model has a lower indoor reflectivity, so that there will be no obvious reflection mirror on the indoor surface under the effect of night lights, and the user's indoor experience will be more comfortable.

[0025] 3. The utility model's neutral color low internal reflection temperable triple-silver low-emissivity coated glass makes the bonding stability between the film layers better, so that the film layers are defect-free after tempering, the color performance is stable, and the temperable effect is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic structural diagram of the tempered triple-silver low-emissivity and low internal reflection coated glass in Example 1 of the utility model.

[0027] Markings in the figure: 1-glass substrate; 2-film layer; 201-first silicon nitride layer; 202-second zinc oxide layer; 203-third silver layer; 204-fourth AZO layer; 205-fifth silicon nitride layer; 206-sixth zinc oxide layer; 207-seventh silver layer; 208-eighth copper layer; 209-ninth nickel-chromium alloy layer; 210-tenth AZO layer; 211-eleventh zinc oxide-tin layer; 212-twelfth zinc oxide layer; 213-thirteenth silver layer, 214-fourteenth nickel-chromium alloy layer, 215-fifteenth AZO layer, 216-sixteenth silicon nitride layer. DETAILED DESCRIPTION

[0028] The utility model is described in detail below in conjunction with the accompanying drawings.

[0029] In order to make the purpose, technical solution and advantages of the utility model more clear, the utility model is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described here are only used to explain the utility model and are not used to limit the utility model.

[0030] Example 1

[0031] A neutral color low internal reflection tempered triple silver low emissivity coated glass ( Figure 1), the film layers of the coated glass are all obtained by sputtering coating through a magnetron sputtering process; it comprises a glass substrate 1 and a film layer 2, wherein the film layer 2 is arranged on the surface of the glass substrate 1; wherein the film layer 2 comprises, from the glass substrate 1 to the outside, a first silicon nitride layer 201 with a thickness of 25 nm, a second zinc oxide layer 202 with a thickness of 9 nm, a third silver layer 203 with a thickness of 7.6 nm, a fourth AZO layer 204 with a thickness of 4 nm, a fifth silicon nitride layer 205 with a thickness of 35 nm, a sixth zinc oxide layer 206 with a thickness of 12.5 nm, a a seventh silver layer 207 with a thickness of 13 nm, an eighth copper layer 208 with a thickness of 4.5 nm, a ninth nickel-chromium alloy layer 209 with a thickness of 2.1 nm, a tenth AZO layer 210 with a thickness of 8 nm, an eleventh zinc oxide tin layer 211 with a thickness of 64 nm, a twelfth zinc oxide layer 212 with a thickness of 14 nm, a thirteenth silver layer 213 with a thickness of 12 nm, a fourteenth nickel-chromium alloy layer 214 with a thickness of 2 nm, a fifteenth AZO layer 215 with a thickness of 4 nm, and a sixteenth silicon nitride layer 216 with a thickness of 32.5 nm;

[0032] The obtained coated glass was tempered, and the optical properties before and after tempering were tested. The results are as follows:

[0033] Transmittance color a* Transmittance b* Indoor reflectivity Before tempering -3.4 +4 4.8 After tempering -4.5 +2.5 5.0

[0034] The triple-silver low-emissivity coated glass achieves the advantages of low internal reflection and a transmitted color close to neutral color by adjusting the composition of each film layer after tempering.

[0035] Example 2

[0036] A neutral color low internal reflection temperable triple silver low emissivity coated glass, wherein the film layers of the coated glass are obtained by sputtering coating through a magnetron sputtering process; the glass substrate 1 and the film layer 2 are provided on the surface of the glass substrate 1; wherein the film layer 2 includes, from the glass substrate 1 to the outside, a first silicon nitride layer 201 with a thickness of 20 nm, a second zinc oxide layer 202 with a thickness of 15 nm, a third silver layer 203 with a thickness of 5 nm, a fourth AZO layer 204 with a thickness of 5 nm, a fifth silicon nitride layer 205 with a thickness of 30 nm, a second zinc oxide layer 206 with a thickness of 15 nm, a third silver layer 207 with a thickness of 5 nm, a fourth AZO layer 208 with a thickness of 5 nm, a fifth silicon nitride layer 209 with a thickness of 30 nm, a fifth nitride layer 201 with a thickness of 15 nm, a fifth nitride layer 202 with a thickness of 15 nm, a fifth nitride layer 203 with a thickness of 30 nm, a fifth nitride layer 204 with a thickness of 30 nm, a fifth nitride layer 205 with a thickness of 15 nm, a fifth nitride layer 206 with a thickness of 15 nm, a fifth nitride layer 207 with a thickness of 30 nm, a fifth nitride layer 208 with a thickness of 30 nm, a fifth nitride layer 209 with a thickness of 30 nm, a fifth nitride layer 209 with a thickness of 30 nm, a fifth nitride layer 201 with a thickness of 30 nm, a fifth nitride layer 202 with a thickness of 30 nm, a fifth nitride layer 203 with a thickness of 30 nm, a fifth nitride layer 204 with a thickness of 30 nm a sixth zinc oxide layer 206, a seventh silver layer 207 with a thickness of 10 nm, an eighth copper layer 208 with a thickness of 3 nm, a ninth nickel-chromium alloy layer 209 with a thickness of 3 nm, a tenth AZO layer 210 with a thickness of 5 nm, an eleventh zinc oxide tin layer 211 with a thickness of 60 nm, a twelfth zinc oxide layer 212 with a thickness of 20 nm, a thirteenth silver layer 213 with a thickness of 10 nm, a fourteenth nickel-chromium alloy layer 214 with a thickness of 3 nm, a fifteenth AZO layer 215 with a thickness of 5 nm, and a sixteenth silicon nitride layer 216 with a thickness of 30 nm;

[0037] The obtained coated glass was tempered, and the optical properties before and after tempering were tested. The results are as follows:

[0038] Transmittance color a* Transmittance b* Indoor reflectivity Before tempering -2.8 +4.7 5.2 After tempering -2.2 +1.2 5.0

[0039] The triple-silver low-emissivity coated glass achieves the advantages of low internal reflection and a transmitted color close to neutral color by adjusting the composition of each film layer after tempering.

[0040] Example 3

[0041] A neutral color low internal reflection temperable triple silver low emissivity coated glass, wherein the film layers of the coated glass are obtained by sputtering coating through a magnetron sputtering process; the glass substrate 1 and the film layer 2 are provided on the surface of the glass substrate 1; wherein the film layer 2 includes, from the glass substrate 1 to the outside, a first silicon nitride layer 201 with a thickness of 30 nm, a second zinc oxide layer 202 with a thickness of 10 nm, a third silver layer 203 with a thickness of 10 nm, a fourth AZO layer 204 with a thickness of 3 nm, a fifth silicon nitride layer 205 with a thickness of 40 nm, a fifth nitride layer 206 with a thickness of 10 nm, and a fifth nitride layer 207 with a thickness of 10 nm. a sixth zinc oxide layer 206, a seventh silver layer 207 with a thickness of 15 nm, an eighth copper layer 208 with a thickness of 6 nm, a ninth nickel-chromium alloy layer 209 with a thickness of 1 nm, a tenth AZO layer 210 with a thickness of 10 nm, an eleventh zinc oxide-tin layer 211 with a thickness of 70 nm, a twelfth zinc oxide layer 212 with a thickness of 10 nm, a thirteenth silver layer 213 with a thickness of 15 nm, a fourteenth nickel-chromium alloy layer 214 with a thickness of 1 nm, a fifteenth AZO layer 215 with a thickness of 3 nm, and a sixteenth silicon nitride layer 216 with a thickness of 40 nm;

[0042] The obtained coated glass was tempered, and the optical properties before and after tempering were tested. The results are as follows:

[0043] Transmittance color a* Transmittance b* Indoor reflectivity Before tempering -3.5 +4.3 4.7 After tempering -3.7 +1.8 5.1

[0044] The triple-silver low-emissivity coated glass achieves the advantages of low internal reflection and a transmitted color close to neutral color by adjusting the composition of each film layer after tempering.

[0045] Comparative Example 1:

[0046] A neutral color low internal reflection temperable triple silver low emissivity coated glass, wherein the film layers of the coated glass are obtained by sputtering coating through a magnetron sputtering process; the coated glass comprises a glass substrate 1 and a film layer 2, wherein the film layer 2 is arranged on the surface of the glass substrate 1; wherein the film layer 2 comprises, from the glass substrate 1 to the outside, a first silicon nitride layer 201 with a thickness of 25 nm, a second zinc oxide layer 202 with a thickness of 9 nm, a third silver layer 203 with a thickness of 7.6 nm, a fourth AZO layer 204 with a thickness of 4 nm, a fifth silicon nitride layer 205 with a thickness of 35 nm, a sixth silicon nitride layer 206 with a thickness of 12.5 nm, and a sixth silver layer 207 with a thickness of 11.6 nm. a zinc oxide layer 206, a seventh silver layer 207 with a thickness of 13 nm, an eighth copper layer 208 with a thickness of 0.0 nm, a ninth nickel-chromium alloy layer 209 with a thickness of 2.1 nm, a tenth AZO layer 210 with a thickness of 8 nm, an eleventh zinc oxide tin layer 211 with a thickness of 64 nm, a twelfth zinc oxide layer 212 with a thickness of 14 nm, a thirteenth silver layer 213 with a thickness of 12 nm, a fourteenth nickel-chromium alloy layer 214 with a thickness of 2 nm, a fifteenth AZO layer 215 with a thickness of 4 nm, and a sixteenth silicon nitride layer 216 with a thickness of 32.5 nm;

[0047] The obtained coated glass was tempered, and the optical properties before and after tempering were tested. The results are as follows:

[0048] Transmittance color a* Transmittance b* internal rebellion Before tempering -6.7 -3.0 3.7 After tempering -5.8 0.0 5.0

[0049] ; Analysis and test results show that the eighth copper layer is not added to the film layer. Although the coated glass achieves a low internal reflection effect after tempering, the transmittance color is green.

[0050] Comparative Example 2:

[0051] A neutral color low internal reflection temperable triple silver low emissivity coated glass, wherein the film layers of the coated glass are obtained by sputtering coating through a magnetron sputtering process; the coated glass comprises a glass substrate 1 and a film layer 2, wherein the film layer 2 is arranged on the surface of the glass substrate 1; wherein the film layer 2 comprises, from the glass substrate 1 to the outside, a first silicon nitride layer 201 with a thickness of 25 nm, a second zinc oxide layer 202 with a thickness of 9 nm, a third silver layer 203 with a thickness of 7.6 nm, a fourth AZO layer 204 with a thickness of 4 nm, a fifth silicon nitride layer 205 with a thickness of 35 nm, a sixth silicon nitride layer 206 with a thickness of 12.5 nm, and a sixth silver layer 207 with a thickness of 11.6 nm. a zinc oxide layer 206, a seventh silver layer 207 with a thickness of 13 nm, an eighth copper layer 208 with a thickness of 2.7 nm, a ninth nickel-chromium alloy layer 209 with a thickness of 2.1 nm, a tenth AZO layer 210 with a thickness of 8 nm, an eleventh zinc oxide tin layer 211 with a thickness of 64 nm, a twelfth zinc oxide layer 212 with a thickness of 14 nm, a thirteenth silver layer 213 with a thickness of 12 nm, a fourteenth nickel-chromium alloy layer 214 with a thickness of 2 nm, a fifteenth AZO layer 215 with a thickness of 4 nm, and a sixteenth silicon nitride layer 216 with a thickness of 32.5 nm;

[0052] The obtained coated glass was tempered, and the optical properties before and after tempering were tested. The results are as follows:

[0053] Transmittance color a* Transmittance b* internal rebellion Before tempering -6.4 -2.6 3.96 After tempering -7.4 0.09 5.7

[0054] ; Analysis of the test results shows that although the eighth copper layer is added to the film layer, the thickness of the copper layer is less than the designed value. Although the coated glass achieves a low internal reflection effect after tempering, the transmitted color will still be green.

[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A neutral color low internal reflection temperable triple silver low emissivity coated glass, comprising a glass substrate (1) and a film layer (2), wherein the film layer (2) is arranged on the surface of the glass substrate (1); characterized in that: The film layer (2) comprises, from the glass substrate (1) outward, a first silicon nitride layer (201) with a thickness of 20-30 nm, a second zinc oxide layer (202) with a thickness of 10-15 nm, a third silver layer (203) with a thickness of 5-10 nm, a fourth AZO layer (204) with a thickness of 3-5 nm, a fifth silicon nitride layer (205) with a thickness of 30-40 nm, a sixth zinc oxide layer (206) with a thickness of 10-15 nm, a seventh silver layer (207) with a thickness of 10-15 nm, an eighth copper layer (208) with a thickness of 3-6 nm, and a 2-layer aluminum foil (209) with a thickness of 10-20 nm. 208), a ninth nickel-chromium alloy layer (209) with a thickness of 1-3 nm, a tenth AZO layer (210) with a thickness of 5-10 nm, an eleventh zinc oxide tin layer (211) with a thickness of 60-70 nm, a twelfth zinc oxide layer (212) with a thickness of 10-20 nm, a thirteenth silver layer (213) with a thickness of 10-15 nm, a fourteenth nickel-chromium alloy layer (214) with a thickness of 1-3 nm, a fifteenth AZO layer (215) with a thickness of 3-5 nm, and a sixteenth silicon nitride layer (216) with a thickness of 30-40 nm.

2. The triple-silver low-emissivity coated glass according to claim 1, characterized in that: The thickness of the first silicon nitride layer (201) is 22-25 nm; the thickness of the fifth silicon nitride layer (205) is 35-38 nm; and the thickness of the sixteenth silicon nitride layer (216) is 34-36 nm.

3. The triple-silver low-emissivity coated glass according to claim 1, characterized in that: The thickness of the third silver layer (203) is 6-8 nm; the thickness of the seventh silver layer (207) is 12-14 nm; and the thickness of the thirteenth silver layer (213) is 10-12 nm.

4. The triple-silver low-emissivity coated glass according to claim 1, characterized in that: The thickness of the ninth nickel-chromium alloy layer (209) is 2-3 nm; the thickness of the fourteenth nickel-chromium alloy layer (214) is 1-2 nm.

5. The triple-silver low-emissivity coated glass according to claim 1, characterized in that: The thickness of the eleventh zinc tin oxide layer (211) is 65-68 nm.

6. The triple-silver low-emissivity coated glass according to claim 1, characterized in that: The thickness of the second zinc oxide layer (202) is 12-14 nm; the thickness of the sixth zinc oxide layer (206) is 11-13 nm; and the thickness of the twelfth zinc oxide layer (212) is 12-15 nm.

7. The triple-silver low-emissivity coated glass according to claim 1, characterized in that: The thickness of the fourth AZO layer (204) is 4-5 nm; the thickness of the tenth AZO layer (210) is 6-8 nm; and the thickness of the fifteenth AZO layer (215) is 3-4 nm.

8. The triple-silver low-emissivity coated glass according to any one of claims 1 to 7, characterized in that: The eighth copper layer (208) has a thickness of 4-5 nm.

Citation Information

Patent Citations

  • A light blue, flexible steel glass with a three-silver low-emissivity coating and its manufacturing process.

    CN106186723B

  • Low-emissivity coated glass

    CN212152091U